Magic, witchcraft, and ghosts in the Enlightenment
1 online resource.
Keywords: "Magic, Witchcraft, and Ghosts in the Age of Enlightenment argues for the centrality of magical practices and ideas throughout the long eighteenth-century. With a broad chronological scope that ranges from the end of the seventeenth century into the early nineteenth century, this volume is useful for undergraduates, postgraduates, scholars as well as those with a general interest in magic, witchcraft, and spirits in the Enlightenment"--